Pregnancy and Covid-19: Some Thing to Worry About? - Samreen Iqbal; Muhammad Majid Ali Jafri (Journal of Bahria University Medical and Dental College, 2021)
Pregnancy is a special time, full of excitement and anticipation, but for expectant mothers facing the outbreak of the coronavirus disease (COVID-19), fear, anxiety and uncertainty are clouding this otherwise happy time. Coronavirus disease 2019 (COVID-19) has led to the deadliest pandemic observed in more than a 100 years.1 Around 131 million women give birth annually. This population is particularly vulnerable to emerging infectious pathogens due to alterations in immune, respiratory, and cardiovascular physiology that occurs during pregnancy. Recent outbreaks of severe acute respiratory syndrome, Middle East respiratory syndrome, influenza H1N1, Ebola virus disease, and Zika virus disease resulted in high rates of maternal morbidity and mortality, fetal loss, and fetal harm. Fortunately early data regarding pregnancy outcomes in COVID-19 are reassuring: maternal outcomes are similar to non-pregnant adults; vertical transmission and neonatal infection are rare. However pregnant women remain at risk of severe disease requiring intensive care, and they deserve equity to access therapeutic options guided by rigorous scientific data.2-3 More than 90% of infected mothers recovered without undergoing delivery.3 Pregnant women should follow the same recommendations as non pregnant individuals to avoid exposure to the virus such as social distancing, hand hygiene, disinfecting surfaces and wearing a mask in public. All pregnant women should be monitored for development of symptoms and signs of COVID-19, particularly if they have had close contact with a confirmed case or persons under investigation. American College of Obstetricians and Gynecologists (ACOG) has developed algorithms to evaluate pregnant outpatients with suspected or confirmed COVID-194.Patients having symptoms compatible with COVID-19, the severity of illness, underlying co-morbidities, and clinical status should be assessed to determine the potential need for hospitalization.